Biology Fisheries of Threadfin Bream Fish (Family: Nemipteridae) Landed at Oeba Fish Landing Site and Oesapa Fish Market, Kupang City - Wora, Umbu Domu; Wijayati, Diah Permata; Widowati, Ita; Nursalim, Nining; Kolilah, Nenik; Ginzel, Fanny Iriyany; Kurniasih, Eka Maya (Jurnal Kelautan Tropis, 2024)
The threadfin bream fish from the Nemipteridae family is a demersal species and an economically significant commercial fish. It is widely used for personal consumption and sold in markets. The capture of threadfin bream fish at the Oeba Fish Landing Site and Oesapa Fish Market has been increasing. Continuous high-intensity fishing will likely negatively impact the threadfin bream fish population, leading to stock depletion and reduced catch production. Research on threadfin bream fish in East Nusa Tenggara has yet to be reported, particularly in Kupang Bay and Rote Ndao waters. This study aims to investigate the fisheries biology of threadfin bream fish landed at the Oeba Fish Landing Site and Oesapa Fish Market. A total of 84 threadfin bream fish were sampled from both locations. The length-weight relationship of threadfin bream fish at these sites is negatively allometric with value b < 3, indicating that length growth is more dominant than weight gain. The gonad maturity stages of male and female threadfin bream fish range from GSM I-III. The size distribution of threadfin bream fish ranges from 173-295 mm at the Oeba Fish Landing Site and from 173-245 mm at the Oesapa Fish Market. Most of the threadfin bream found are still in the early stages of gonadal maturity, indicating that these fish are young and not yet ready to spawn. Implementing Sustainable fishing management practices is crucial, including setting catch quotas and minimum catch sizes and educating fishermen to ensure the sustainability of threadfin bream fish stocks.